Ethical and Legal Considerations for Scientists Collaborating with Whalers: A Case Study of International Research Using the Outcome of Contemporary Whaling by Iceland. Issue 1 (3rd April 2021) - Ryan, Conor; Papastavrou, Vassili; Sand, Peter H.
Abstract: This article explores some ethical and legal issues regarding international research conducted on whales killed by Iceland since it resumed whaling in 2003. In total, 35 peer-reviewed publications and 11 conference presentations were identified, wherein international research directly or indirectly relied on contemporary whaling for samples or data. The authors of these publications were affiliated with 56 institutions from 13 countries. Parallels are drawn between this research and the offshoring of biomedical research that exploited weaker regulations elsewhere. Ethical assessments were rarely included in the reviewed papers, and none of them addresses the issue of compatibility with the International Convention for the Regulation of Whaling (ICRW) or with the laws and ethical standards within the countries where the researchers are based. Diplomatic efforts to uphold international treaties to protect whales may be undermined by research using the outcome of whaling. Government grants were used by research institutions in four ICRW member countries (Spain, Sweden, the United Kingdom, and the United States) where the governments had formally objected to Iceland's reservation against the ICRW whaling moratorium. Researchers and their institutions may become tacitly complicit in contemporary commercial and alleged scientific whaling, when these activities may not be consistent with the ethical standards or laws within their own countries. Greater transparency is needed among academic institutions, government agencies, nongovernmental organizations, funding bodies, journals, and professional societies regarding legal and ethical issues when data or samples from such whaling operations are used. Ethical frameworks need to be developed analogous to those used in international biomedical research and other disciplines.